Early invasive versus early conservative strategy in non-ST-elevation acute coronary syndrome: An outcome research study. Issue 6 (1st September 2017) - Tubaro, Marco; Sciahbasi, Alessandro; Ricci, Roberto; Ciavolella, Massimo; Di Clemente, Domenico; Bisconti, Carmela; Ferraiuolo, Giuseppe; Del Pinto, Maurizio; Mennuni, Mauro; Monti, Francesco; Vinci, Eugenio; Semeraro, Raffaella; et al.
Abstract: Background: An early invasive strategy (EIS) has been shown to yield a better clinical outcome than an early conservative strategy (ECS) in patients with non-ST-elevation acute coronary syndromes (NSTEACSs), particularly in those at higher risk according to the GRACE risk score. However, findings of the clinical trials have not been confirmed in registries. Objective: To investigate the outcome of patients with NSTEACS treated according to an EIS or a ECS in a real-world all-comers outcome research study. Methods: The primary hypothesis of the study was the non-inferiority of an ECS in comparison with an EIS as to a combined primary end-point of death, non-fatal myocardial infarction and hospital readmission for acute coronary syndromes at one year. Participating centres were divided into two groups: those with a pre-specified routine EIS and those with a pre-specified routine ECS. Two statistical analyses were performed: a) an 'intention to treat' analysis: all patients were considered to be treated according to the pre-specified routine strategy of that centre; b) a 'per protocol' analysis: patients were analysed according to the actual treatment applied. Cox model including propensity score correction was applied for all analyses. Results: The intention to treat analysis showed an equivalence between EIS and ECS (11.4% vs . 11.1%) with regard to the primary end-point incidence at one year. In the three subgroups of patients according to the GRACE risk score (⩽ 108, 109–140, > 140), EIS and ECS confirmed their equivalence (5.3% vs . 3.9%, 8.4% vs . 7.6%, and 20.3% vs . 20.9%, respectively). When the per protocol analysis was applied, a reduction of the primary end-point at one year with EIS vs . ECS was demonstrated (6.2% vs . 15.3%, p =0.021); analysis of the subgroups according to the GRACE risk score numerically confirmed these data (3.1% vs . 6.5%, 5.1% vs . 10.0%, and 10.8% vs . 24.5%, respectively). Conclusions: In a real-life registry of all-comers NSTEACS patients, ECS was non-inferior to EIS; however, when EIS was applied according to clinical judgement, a reduction of clinical events at one year was demonstrated.